Report of the Steering Group on Education for the Fifth Five Year Plan - Planning Commission (Planning Commission, 1973)
The composition of the Task Forces and the Steering Group is given in Appendix I. All the Task Forces except those on Youth, Physical Education, Games & Sports and Educational Finance have exported while the Task Force on Youth, Physical Education, Games & Sports has yet to submit its report, that on Educational Finance has initiated certain studies which will take considerable time before their results will be available.
Education Division Planning Commission Government of India
Education Division Planning Commission Government of India